Suicidal ideation and thoughts of self-harm during the COVID-19 pandemic among Swedish employees: a cohort study on the role of job instability and job insecurity - Sandra Blomqvist; Hugo Westerlund; Linda L. Magnusson Hanson (BMC Psychology, 2024)
Abstract Background Suicidal ideation may be a warning sign for suicide and previous work has indicated a higher prevalence of suicidal ideation during the COVID-19 pandemic. Job loss and job insecurity are potential risk factors for suicidal ideation, but their importance during the pandemic, and the role of organizational changes for suicidal ideation, is unclear. This study examined the association between various experiences associated with job loss and job insecurity during the pandemic and thoughts of suicide/self-harm in Sweden. Methods The study sample was drawn from the Swedish Longitudinal Occupational Survey of Health (SLOSH). Auxiliary data collections in February 2021 and 2022 assessed exposure to job loss/unemployment, furlough, workplace downsizing, or increased job insecurity versus stable employment and thoughts of suicide or self-harm (PHQ-9) during the pandemic. The analyses were based on 1558 individuals (2 349 observations) participating in either or both waves and who had been working before the pandemic. Logistic regression models with cluster-robust standard errors were fitted, including sociodemographic factors and prior mental health problems to control for potential confounding. Measures of personality based on a brief version of the Big-Five personality inventory were also added. Results The results indicated an association between all experiences, except furlough, and thoughts of suicide/self-harm, when adjusting for sex, age, civil status, socioeconomic status and prior mental health (job loss odds ratio (OR) = 3.70, 95% confidence interval (CI) 1.79–7.63, downsizing OR = 2.41, CI 1.24–4.70, job insecurity OR = 2.77, CI 1.15–6.67). The associations for job loss and insecurity were attenuated by adjustment for personality, although it remained statistically significant for downsizing. Conclusions The results suggested a higher risk of suicidal ideation connected with loss of employment and survival of a downsizing, but not a forced reduction in working times/pay during the COVID-19 pandemic. The association for subjective job insecurity was less robust and may be partly explained by personality.